“Expecting the unexpected?” Uncovering role expectation differences in a Dutch hospital - Wolffgramm, Milan; Bücker, Joost; Van der Heijden, Beatrice (Frontiers in Psychology, 2022)
The aim of this study was to empirically investigate differences in role expectations, among the stakeholders involved, about the devolved personnel management role of front-line managers (FLMs). In particular, we researched the role expectation differences between FLMs, their middle managers, and Human Resource (HR) practitioners. In total, nineteen semi-structured interviews have been conducted involving eleven FLMs, eight middle managers, and two HR practitioners working at the same Dutch hospital. Most discovered role expectation differences were related to how FLMs should execute their HR tasks (i.e., process ambiguity). FLMs were often uncertain if their role enactment met those of their middle managers and/or HR practitioners, herewith indicating role stress. Our findings underline the importance of paying attention to role expectations’ differences in aligning components of the HRM-performance relationship. Future research could include the role expectations of other important stakeholders, such as: subordinates and top management. The outcomes of this empirical work are translated into four interventions to diminish FLMs’ role stress.